The Workplace and Teacher’s Certification for Teacher’s Performance - Sulastri, Titha; Kristiawan, Muhammad; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to identify the impact of the workplace and teacher’s certification on teacher’s performance. This study was conducted at State Vocational Schools in the Ogan Komering Ilir district, with 95 teachers serving as participants. This study is quantitative by using questionnaires, interviews, and documentation as instruments. Validity and reliability tests were performed on the research instrument, as well as prerequisite tests for analysis of normality, linearity, multicollinearity, and heteroscedasticity tests. Descriptive analysis, simple linear regression, multiple regression correlation, and the coefficient of determination were used to analyze the data. The findings indicate that the workplace and teacher’s certification have an impact on teacher’s performance.